2012
DOI: 10.1073/pnas.1213770110
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the activation mechanism of the PlcR virulence regulator by the quorum-sensing signal peptide PapR

Abstract: The quorum-sensing regulator PlcR is the master regulator of most known virulence factors in Bacillus cereus. It is a helix-turn-helix (HTH)-type transcription factor activated upon binding of its cognate signaling peptide PapR on a tetratricopeptide repeat-type regulatory domain. The structural and functional properties of PlcR have defined a new family of sensor regulators, called the RNPP family (for Rap, NprR, PrgX, and PlcR), in Gram-positive bacteria. To fully understand the activation mechanism of PlcR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 35 publications
4
100
0
3
Order By: Relevance
“…Both PrgX and PlcR regulate the transcription of their target genes in response to a signal peptide. Peptide binding to PlcR enhances DNA binding through drastic conformational and oligomerization changes promoting transcription activation of cognate target genes (58,59). In contrast, PrgX responds to two competing signaling peptides and acts as a transcriptional repressor.…”
Section: Resultsmentioning
confidence: 99%
“…Both PrgX and PlcR regulate the transcription of their target genes in response to a signal peptide. Peptide binding to PlcR enhances DNA binding through drastic conformational and oligomerization changes promoting transcription activation of cognate target genes (58,59). In contrast, PrgX responds to two competing signaling peptides and acts as a transcriptional repressor.…”
Section: Resultsmentioning
confidence: 99%
“…S3 A-C) (33) and the RNPP proteins PlcR and PrgX (Fig. S3 D-F) (15,34); however, in the Rgg2 Sd structure (and the Rgg Sd -CsA structure described below) the Rgg2 Sd DBDs are covalently linked across the dimerization interface by a disulfide bond between the α4 helices ( Fig. 2A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Rap proteins are phosphatases and transcriptional antiactivators, whereas NprR, PlcR, and PrgX are DNA-binding transcription factors. Structure-function studies revealed that Rap, NprR, PlcR, and PrgX (the RNPP family proteins) use a structurally similar C-terminal tetratricopeptide (TPR)-like repeat domain to bind their cognate peptide pheromones (12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Together, these findings strongly indicated that the microbial product was not a peptide, the typical type of quorumsensing molecules used by gram-positive bacteria, 28 including B. cereus. 29 It is possible that the product that elicited the response was not unique to B. cereus and may be shared by pathogens more commonly associated with respiratory disease. Although the specific identity of the active B. cereus CM product remains unknown, high-performance liquid chromatography (HPLC) and mass spectroscopy are feasible future options for isolation and identification.…”
Section: Discussionmentioning
confidence: 99%